prove that log tan1 + log tan2+......+log tan 89 = 0
Answers
Answered by
5
Heya User,
--> Rules used --> log a + log b = log [ a * b ]
--> tan a * tan ( 90 - a ) = 1
Now, ATQ -->
--> log tan(1) + log tan(2) + ... + log tan(89)
= log ( tan(1) * tan(2) * ... * tan(89) )
= log [ ( tan 1 * tan 89 ) ... ( tan 44 * 46 ) * tan 45 ]
= log [ 1 * 1 * 1 * 1 * .... * 1 ] ----> [ tan 45 = 1 ]
= log 1 = 0
Hence, proved ^_^
--> Rules used --> log a + log b = log [ a * b ]
--> tan a * tan ( 90 - a ) = 1
Now, ATQ -->
--> log tan(1) + log tan(2) + ... + log tan(89)
= log ( tan(1) * tan(2) * ... * tan(89) )
= log [ ( tan 1 * tan 89 ) ... ( tan 44 * 46 ) * tan 45 ]
= log [ 1 * 1 * 1 * 1 * .... * 1 ] ----> [ tan 45 = 1 ]
= log 1 = 0
Hence, proved ^_^
Similar questions